Dubious or disappeared phanerogamic species from Romania (II) - Denes PAZMANY; Eugenia CHIRCA (Notulae Botanicae Horti Agrobotanici Cluj-Napoca, 1992)
In this second paper are presented 29 monocolamydeous and dyalipetalous Dicotyledonatae species, 20 of which emphasized by a frame, are considered to be disappeared definitely from Romanian flora.